What the SIF Is Happening—The Role of Intracellular Salmonella-Induced Filaments - Knuff, Katelyn; Finlay, B. Brett (Frontiers in Cellular and Infection Microbiology, 2017)
A common strategy among intracellular bacterial pathogens is to enter into a vacuolar environment upon host cell invasion. One such pathogen, Salmonella enterica, resides within the Salmonella-containing vacuole (SCV) inside epithelial cells and macrophages. Salmonella hijacks the host endosomal system to establish this unique intracellular replicative niche, forming a highly complex and dynamic network of Salmonella-induced filaments (SIFs). SIFs radiate outwards from the SCV upon onset of bacterial replication. SIF biogenesis is dependent on the activity of bacterial effector proteins secreted by the Salmonella-pathogenicity island-2 (SPI-2) encoded type III secretion system. While the presence of SIFs has been known for almost 25 years, their precise role during infection remains elusive. This review summarizes our current knowledge of SCV maturation and SIF biogenesis, and recent advances in our understanding of the role of SIFs inside cells.